Dayak People’s Spirituality and Local Wisdom in Preserving Nature and Transforming Social Life in Gunung Mas Regency Central Kalimantan - Desie Andreastuti (UIN Siber Syekh Nurjati Cirebon, 2025)
This study employs an integrative literature review approach to examine how the spirituality and local wisdom of the Dayak community in Gunung Mas Regency, Central Kalimantan shape patterns of social governance and support broader processes of social transformation. Unlike empirical studies that rely on interviews, surveys, or field observations, this research synthesizes multidisciplinary findings drawn from anthropology, the sociology of religion, public administration, environmental governance, and customary law. The reviewed literature consistently illustrates that Dayak spirituality embodied in ritual practices, moral teachings, and adat-based norms operates as a comprehensive normative system that guides everyday social conduct, regulates relationships within the community, and structures mechanisms of conflict resolution and social protection. Furthermore, the synthesis demonstrates that this spiritual foundation plays a crucial role in shaping community-based environmental management, emphasizing harmony with nature, collective stewardship, and intergenerational responsibility. Building on these insights, the study proposes a conceptual model of spiritual governance, which highlights the integration of cosmological values, collective obligations, relational accountability, and adaptive decision-making processes within Dayak communal life. The findings enrich theoretical discussions on culturally rooted governance by illustrating how spiritual–ethical frameworks can function as legitimate sources of authority and organizational coherence. This study also offers new perspectives for public administration, particularly regarding the relevance of indigenous spiritual ethics in advancing inclusive, context-sensitive, and sustainable governance practices.